Desenvolvimento de método analítico paradeterminação multirresíduo de agrotóxicos em abacaxi utilizando as técnicas QuEChERS E CG/EM - Barbosa, Pablo Gordiano Alexandre (2013)
The development of analytical methods for multiresidue determination of pesticides in food is essential for the efficient monitoring of these compounds in products consumed by the population, enabling regulators to obtain faster and reliable results. This study aimed to the development and validation of a method based on techniques modified QuEChERS-citrate and gas chromatography-mass spectrometry (GC/MS) for the multiresidue determination of 45 pesticides in fruits of pineapple. The method was validated by determining the selectivity, linearity, limit of detection (LOD), limit of quantification (LOQ), precision and accuracy, being configured with detection based on electron impact ionization (EI) and selected ion monitoring (SIM). The method was satisfactory selectivity for all target compounds, except chloroneb. Limits of detection ranged from 0.005 mg/kg and 0.05 mg/kg and limits of quantification between 0.015 mg/kg and 0.09 mg/kg. The linearity was adequate for most analytes at a range of concentration of 0.01 to 0.75 mg/kg with correlation coefficients ranged from 0.9593 to 0.9996. Of pineapple samples analyzed, applying the developed method, were detected the pesticides fenpropathrin, pyraclostrobin, ametryn, triflumizole and trifluralin.